Inhalation‐Driven Vertical Flutter Triboelectric Nanogenerator with Amplified Output as a Gas‐Mask‐Integrated Self‐Powered Multifunctional System. Issue 31 (31st May 2022) - Heo, Deokjae; Song, Myunghwan; Chung, Seh‐Hoon; Cha, Kyunghwan; Kim, Youna; Chung, Jihoon; Hwang, Patrick T.J.; Lee, Jaeheon; Jung, Heesoo; Jin, Youngho; Hong, Jinkee; Kim, Min‐Kun; et al.
Abstract: With the widespread use of sensors and small electronics in the Internet of Things (IoT) era, triboelectric nanogenerators (TENGs) have emerged as sustainable and renewable energy sources owing to their high efficiency, compatibility with various materials, and low cost. However, the existing TENGs exhibit a low current output and require a large mechanical input to continuously generate an enhanced current output. In this study, an inhalation‐driven vertical flutter TENG (IVF‐TENG) with an amplified current output is developed. The IVF‐TENG exhibits two types of mechanical behaviors simultaneously, generating a high‐frequency continuous electrical voltage and closed‐circuit current ( I CC ) output of 17 V and 1.84 μA, respectively, during inhalation, and an electrostatic discharge voltage and I CC output of 456 V and 288 mA at the beginning and end of every inspiratory cycle, respectively. As a user‐position‐indicating light, the IVF‐TENG can power 130 LEDs in series and 140 LEDs in parallel for every inhalation. The IVF‐TENG can charge a capacitor of 660 μF, with a discharge process of a few seconds, to power a commercial Bluetooth tracker and wirelessly transfer the Bluetooth signal to a smartphone. Moreover, the IVF‐TENG can detect the user's respiration state or the presence of chemical warfare agents (GB, DMMP, etc.) via output waveforms. Abstract : The inhalation‐driven vertical flutter triboelectric nanogenerator (IVF‐TENG) generates two types of electrical outputs (continuous output and electrostatic discharge output) for every inhalation cycle owing to vertical flutter motion. The IVF‐TENG can function as a gas mask‐integrated self‐powered multifunctional system (self‐powered user‐position‐indicating light, auxiliary power source, user's respiration state detector, and chemical warfare agents sensor).